2010
DOI: 10.1007/s12600-010-0105-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weedy field margins on abundance patterns of the predatory bugs Orius spp. and their prey, the western flower thrips (Frankliniella occidentalis), on faba bean

Abstract: The influence of weedy field strips on the abundance patterns of western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), and predatory bugs of Orius spp. (Hemiptera: Anthocoridae), on faba bean and on weeds was investigated in Adana province, Turkey, during 2005-2006. There were two treatments: in one treatment, weeds at the margins and inside the plots were regularly controlled by tillage; in the other treatment no weed control was done. Thrips and Orius were sampled by beating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
4
29
0
1
Order By: Relevance
“…Other work has shown that this bug changes its preference for oviposition sites on a plant species depending on whether it was offered singly or with other plants (Lundgren & Fergen, ), whereas other work shows that different combinations of plant species did not influence the proportion of eggs laid by O. insidiosus on each plant species (Coll, ) (although this study just examined small cuttings of trifoliates). Atakan () found that O. insidiosus may prefer fava bean plants as a site for egg laying when it was compared with many other plants. In the first experiment, O. insidiosus females raised on fava beans with covered nectaries survived well relative to the other plant species when their flowers were covered, which is consistent with the hypothesis that vegetative structures of fava beans may have good nutrition for maintaining O. insidiosus survival.…”
Section: Discussionmentioning
confidence: 99%
“…Other work has shown that this bug changes its preference for oviposition sites on a plant species depending on whether it was offered singly or with other plants (Lundgren & Fergen, ), whereas other work shows that different combinations of plant species did not influence the proportion of eggs laid by O. insidiosus on each plant species (Coll, ) (although this study just examined small cuttings of trifoliates). Atakan () found that O. insidiosus may prefer fava bean plants as a site for egg laying when it was compared with many other plants. In the first experiment, O. insidiosus females raised on fava beans with covered nectaries survived well relative to the other plant species when their flowers were covered, which is consistent with the hypothesis that vegetative structures of fava beans may have good nutrition for maintaining O. insidiosus survival.…”
Section: Discussionmentioning
confidence: 99%
“…There are many laboratory predation studies of Orius spp. on thrips, as well as some under field conditions in the Mediterranean basin and the Middle East . However, very little is known about Orius spp.…”
Section: Introductionmentioning
confidence: 99%
“…on thrips, 9 -14 as well as some under field conditions in the Mediterranean basin and the Middle East. 3,15 -17 However, very little is known about Orius spp. predation on N. ribisnigri and F. occidentalis, as well as on other pests, alternative prey or even natural enemies, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The range of values obtained for pest control varied considerably (Table ). The highest value for pest reduction in the field was obtained from Atakan () in which it was shown that infestation of the western flower thrips ( Frankliniella occidentalis Pergande) on faba bean ( Vicia faba L.) was reduced by a maximum of 98% due to weedy margins that hosted beneficial insects. For pest predation, the highest value was obtained in a laboratory experiment by Araj and Wratten (), in which they demonstrated that the predation of cabbage aphids Brevicoryne brassicae L. on Capsella bursa‐pastoris L. increased by 255%.…”
Section: Resultsmentioning
confidence: 99%